2012
DOI: 10.1007/s12070-012-0583-9
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Peripheral Osteoma of the Mandible with Case Series and Review of Literature

Abstract: Osteomas are benign lesions composed of mature compact and cancellous bone usually arising from craniofacial region. They can be central or peripheral, solitary or multiple. We are presenting few cases of giant peripheral osteoma's of the mandible along with review literature of other jaw lesions with their diagnostic features and differential diagnosis. The purpose of presenting this paper is to evaluate radiopaque lesions of the jaw which require proper clinical and histological evaluation to reach a final d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 21 publications
(25 reference statements)
0
21
0
Order By: Relevance
“…According to Soni et al the prevalence of osteomas in the normal population is about 4 %. [9] Peripheral osteoma occurs most frequently in the frontal, ethmoid, and maxillary sinuses but are not common in jawbones. [10,11] A review of the literature revealed that mandible is more commonly affected than the maxilla.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…According to Soni et al the prevalence of osteomas in the normal population is about 4 %. [9] Peripheral osteoma occurs most frequently in the frontal, ethmoid, and maxillary sinuses but are not common in jawbones. [10,11] A review of the literature revealed that mandible is more commonly affected than the maxilla.…”
Section: Discussionmentioning
confidence: 99%
“…[15] It is reported that these lesions are more predominant in females by a ratio of 3:1. [10,11,12] Some studies, show that osteomas are more frequent in males than in females [5] S. Soni et A. Bhargava [9] reported that there is no predilection for sex.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5,14,18 In addition, the osteoid subtype of osteomas usually grows rapidly and is painful. 14,19 A periosteal osteoblastoma has similar characteristics in terms of growth rate and symptoms. 14,19 Similar to an osteoma, a peripheral ossifying fibroma appears as a radiopaque mass; however, it does not intrude into the cortical bone.…”
Section: 410mentioning
confidence: 99%